Scaling-up the production of 13s-hydroxy-9Z,11E-octadecadienoic acid (13S-HODE) through chemoenzymatic technique - Omar, Muhammad Nor; Moynihan, Humphrey; Hamilton, Richard J. (Korean Chemical Society, 2003)
In spite of greater use of oils and fats in the food industry, the other applications have not been explored very much. Beside the oleochemical industry, the other areas that attract greater interest nowadays are the utilization of fatty acids and their derivatives in pharmaceutical applications. While most fatty acids are achiral molecules, this lack of chirality becomes a great challenge to the chemists to look into possibilities of transforming them into highly value-added chiral molecules which exhibit a vast variety of biological roles in plants and mammals. The most popular technique to transform achiral fatty acids into their corresponding chiral metabolites is through biotechnology processes.1 With the increasing demands for microbial and enzymatic biotransformation, the search for new biologically active substances has been given great attention. In the case of linoleic acid 1, the enzyme which can transform the acid into a chiral hydroperoxide, i.e. 13S-hydroperoxy-9Z,11E-octadecadienoic acid (13S-HPOD, 2) is called lipoxygenase (LOX). 13SHPOD is a precursor for the formation of 13S-hydroxy-9Z,11E-octadecadienoic acid (13S-HODE, 3) (Scheme 1).